The Effect of Public Service Motivation on Integrated Administration Services at District Level of Government - Tahili, Mashuri H. (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2018)
This article seeks to analyze the effect of public service motivation on district integrated administration service (PATEN) at Simpang Raya District in Banggai Regency, Central Sulawesi Province. Many researches only analyzed the outcomes of public service motivation and performance. Meanwhile, this article focuses on investigating the association between public service motivation based on Perry’s theory involved four dimensions, such as attractive in public policy making, attractive commitment to public duties, compassion, and self sacrifice toward district integrated administration service by using the theory of Individual Work Performance (IWP) consisting of three dimensions, namely, task performance, performance contextual, and counterproductive behavior. The research approach is quantitative by means of a survey conducted over 195 samples which are gained by using purposive technique. Uses data are analyzed using structural equation modelling. The research findings show that public service motivation is significantly influenced towards the district integrated administration service (PATEN) at Government of Simpang Raya District in Banggai Regency, Central Sulawesi Province. The results of this research confirmed that Public Service Motivation theory found that value of CMIN = 406.681, Significance = 0,00001, Df = 221, Ratio = 1.840, PCFI = 0.655, PNFI = 0.517, and RMSEA = 0.066. The most influential indicators of public service motivation are (1) commitment to civic duties (0.94); (2) self sacrifice (0.83); (3) compassions (0.79); and (4) attractive to public policy making (0.38). The public service motivation variable is estimated to gain by approximately 44,6% to district integrated administration service (PATEN) at government of Simpang Raya District in Banggai Regency, Central Sulawesi Province.